(untitled) (Tokyo, Japan, 1985)
Contents: Part 1. Recent trends in small and medium enterprises; Part 2. Tasks for small and medium enterprises in the age of innovation; Conclusion; Focuses in the fy 1985 measures for small and medium enterprises.
Keywords: Doanh nghiệp nhỏ,Small business; Nhật Bản,Japan